Was dirigiert der Dirigent? Celibidache, Toscanini und die Dialektik des Musikalischen - Kabisch, Thomas (Die Musikforschung, 2005)
Orchestral playing differs from chamber music insofar as the activities of reading the score and playing the instrument are separated. Musical performance, however, works essentially the same way in both cases: Reading the score (whether by a conductor or by the players themselves) terminates - has to terminate - in a well-defined problem which is grasped and solved by the performers. Under such circumstances to practise a piece, a passage or a instrumental part means to weigh possible solutions according to the potentiality of the particular musician. Excerpts from Hans Keller, Johann Joachim Quantz and Leopold Mozart are discussed; two performances of Claude Debussy's "Nuages" are compared.